Improving the skills to make a wallet manic-acrylic beads through cooperative learning for mild mental retardation child class X SLB N 1 Padang - Willya Zetira (Universitas Negeri Padang, 2016)
This research is motivated by the problems found in SLB Negeri 1 Padang. A student mild mental retardation X. class of four found two students experiencing mild mental retardation problem in making skills wallet acrylic beads. The method used is action research class of II cycle. Each siklu consists of five face-to-face meetings and one meeting of the evaluation cycle conducted in several stages yaiut planning, action, observation and reflection. Data collection techniques are observation, documentation and testing. The results showed that cooperative learning can enhance the skills of making purses manic-manic acrylic for retarded children in class X in SLB Negeri 1 Padang